"Tira con tirita y ojal con botón". Memory, imagination and affections to narrate the childhood experiencies of exile (Clepsidra - Interdisciplinary Journal of Memory Studies, 2023)
Addressing the absence of the sons and daughters exile from the academic field of post-dictatorship memory, this article considers the impact of foreign exile on those who were born and/or raised far from the Southern Cone. I consider three literary works (De exilios, maremotos y lechuzas de Carolina Trujillo [1990], El azul de las abejas by Laura Alcoba [2015] and Mi exilio dorado de Marco Fajardo [2021]) and two documentaries (Hora chilena [2013] and Tus padres volverán [2015]) that reflect a generational community that was, and continues to be, dispersed across a variety of linguistic and cultural spaces. These experiences permit a more nuanced analysis into the ‘golden exile’ myth, through which exile has been portrayed as a space of privilege. By incorporating these often-neglected voices, this article reveals the ways in which exile continues to affect their lives.